Low-carbon city initiatives and firm risk: A quasi-natural experiment in China - Huang, Jingchang; Cao, June; Hasan, Tahseen; Zhao, Jing (Journal of Financial Stability, 2021)
This study contributes to the low-carbon city (LCC) related literature by providing causal evidence on the impact of carbon reduction regulation on firm risk. Using staggered adoption of LCC program shocks in China as a quasi-natural experiment, we implement a difference-in-differences (DiD) analysis to investigate the impact of the low-carbon city initiatives on firm risk. We find that low-carbon city initiatives are significantly correlated with firm total risk, systematic risk, and idiosyncratic risk. The results are more pronounced for firms with greater changes of investment in fixed assets and R&D and for firms in provinces with stronger legal enforcement. Our study provides in-depth insights into the low-carbon city initiatives and the firm-level impact of its implementation.